Bench Scale Study of ethyl alcohol Production from Molasses Using Saccharomyces cerevisiae (Chemical Engineering Research Bulletin, 2008)
Production of ethyl alcohol from molasses was studied using a standard strain of S. Cerevisiae (Bangladesh Type Culture Collection, BTCC 281) to find out optimal fermentation conditions. The operating variables considered were initial equivalent sucrose concentration and initial pH in the substrate media. The temperature was maintained at 26Â°C throughout the study. In the laboratory scale study, maximum ethanol yield percent was found to be around 68 at initial equivalent sucrose concentration of 16.75 weight percent and at initial pH 4.5. Using similar operating conditions bench scale fermentation studies were carried out in a batch fermenter of 20 liter capacity. Ethanol yield percent was found to be 97.18 at equivalent sucrose concentration of 11.25 weight percent and at initial pH of 4.5.Chemical Engineering Research Bulletin 10 (2006) 40-52